Beyond the Eagle's Shadow : New Histories of Latin America's Cold War - Moreno, Julio, 1970- (Book collections on Project MUSE., 2013)
""This book seeks to complicate our understanding of the Cold War in Latin America by moving beyond simple polarities of East-vs-West. In a series of essays, it looks at ways in which ordinary Latin Americans determined their own history by bending the Cold War to local purposes"--Provided by publisher"--